QUANTITATIVE STUDIES ON THE PRECIPITIN REACTION : EFFECT OF SALTS ON THE REACTION - Heidelberger, Michael (The Rockefeller University Press, 1936)
1. A quantitative study has been made of the effect on the precipitin reaction between the specific polysaccharide of Type III pneumococcus and the homologous antibody of salt concentrations ranging from O.1 M to 1.79 M, including the effect of ions of higher valence. 2. Within these limits, observed decreases in precipitated antibody with increasing salt concentration appear to be due to a decrease in the amount of antibody combined with the S III, rather than to an increase in solubility of the S III-antibody compounds. 3. The egg albumin-antibody reaction is far less sensitive to changes in salt concentration than is the S III-antibody reaction.